3D spatial reconstruction of macroscopic austenite–martensite transition zones in NiTi wires induced by tension and twisting using diffraction/scattering computed tomography. (1st October 2021) - Sedlák, P.; Frost, M.; Ševčík, M.; Seiner, H.
Abstract: Macroscopic austenite–martensite transition zones in thin superelastic NiTi wires subjected to stretching, twisting and their combination were reconstructed via diffraction/scattering computed tomography. The method allows to visualize spatial distributions of both phases from a series of X-ray diffraction scans. A cone-shaped, radially symmetric transformation front was observed in stretched wire both with and without applied pre-twist. Twisting of a pre-stretched wire (with a cone-shaped transformation band front already developed) led to the formation of a multi-prong localization morphology recognizable on the surface. Transition zones in these cases are highly heterogeneous complex 3D objects exhibiting distinct phase gradients; the longitudinal size of the zones is comparable with the wire diameter. In contrast, localized martensitic strips parallel with wire axis and with a wedge-like cross-section appeared on the surface of the wire which was twisted only. We discuss the observed localization patterns with respect to current computational simulations and micromechanical models.